2018
DOI: 10.1007/s11606-018-4710-5
|View full text |Cite
|
Sign up to set email alerts
|

Army and Navy ECHO Pain Telementoring Improves Clinician Opioid Prescribing for Military Patients: an Observational Cohort Study

Abstract: BackgroundOpioid overdose deaths occur in civilian and military populations and are the leading cause of accidental death in the USA.ObjectiveTo determine whether ECHO Pain telementoring regarding best practices in pain management and safe opioid prescribing yielded significant declines in opioid prescribing.DesignA 4-year observational cohort study at military medical treatment facilities worldwide.ParticipantsPatients included 54.6% females and 46.4% males whose primary care clinicians (PCCs) opted to partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Many respondents reported that improved confidence enhanced their ability to talk to patients about their pain care. Respondents who were prescribers described increased comfort in reducing the use of opioids similar to other studies and as shown quantitatively (14)(15)(16)(17). Some reported improved job satisfaction.…”
Section: Discussionsupporting
confidence: 77%
“…Many respondents reported that improved confidence enhanced their ability to talk to patients about their pain care. Respondents who were prescribers described increased comfort in reducing the use of opioids similar to other studies and as shown quantitatively (14)(15)(16)(17). Some reported improved job satisfaction.…”
Section: Discussionsupporting
confidence: 77%
“…Conversely, referrals for behavioral health and physical therapy increased (p < 0.001). Two other studies, by Katzman and colleagues 61 and Frank and colleagues, 59 examined prescription and referral rates, respectively. Katzman and colleagues 61 inspected opioid prescription rates across 1382 clinics associated with the Army and Navy, 99 of which participated in an EELM.…”
Section: Patient-related Outcomesmentioning
confidence: 99%
“…Two other studies, by Katzman and colleagues 61 and Frank and colleagues, 59 examined prescription and referral rates, respectively. Katzman and colleagues 61 inspected opioid prescription rates across 1382 clinics associated with the Army and Navy, 99 of which participated in an EELM. Compared with patients of providers who did not participate in EELM (n = 1,187,945), those with providers who did participate (n = 52,941) observed a much greater decline in prescriptions: from 23 to 9% (p < 0.001).…”
Section: Patient-related Outcomesmentioning
confidence: 99%
“…Katzman et al studied 99 clinics who attended ECHO and compared them to 1283 clinics that did not participate in ECHO. The clinics that attended ECHO had a greater percent decline than the comparison clinics in the number of opioid users, annual opioid prescriptions per patient, average MED prescribed per patient per year, days of co-prescribed opioid and benzodiazepine per opioid user per year [8].…”
Section: Discussionmentioning
confidence: 92%
“…Tele-mentoring educational programs are a novel approach to bringing knowledge to remote and underserved settings. In recent years, these programs have expanded in Canada [7] and around the world [8]. Project Extension for Community Healthcare Outcomes (ECHO) is a tele-mentoring program that started with the need to provide care to hepatitis C patients in rural areas of New Mexico [9].…”
Section: Introductionmentioning
confidence: 99%